A Study on Safety Behaviour in Selected Glove Production Company - Paramasivam, Theepa; Vejayaratna, Navaratnam; Paramasivam, Kumaresh; James, Shri Dayalam; Shukri, Nadin Nadhirah Mohd; Nordin, Mohd Norazmi; Esam, Asrizam (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study was conducted to investigate the correlation between safety climate practices namely management commitment, safety training, workers’ involvement in safety, which serve as independent variables to the compliance to safety behaviour namely safety compliance and safety participation as the dependent variable. In this study, the data was collected from 133 samples who were the employees of local glove production company which includes management staff and non-management staff. Management staff refer to those who are in position as clerk, executives and managers. The findings revealed that safety climates practices consist of management commitment, safety training, workers’ involvement in safety significantly correlated with both safety behaviour dimensions.